Frequency selective human-centric sub 6 GHz electromagnetic measurements in shopping mall - Doruntinë Berisha; Valdete Rexhëbeqaj-Hamiti; Jeta Dobruna; Hëna Maloku; Zana Limani Fazliu; Mimoza Ibrani (Cogent Engineering, 2024)
AbstractLimiting human exposure to radio frequency electromagnetic fields in crowded indoor public spaces such as shopping malls, is identified as one of the key metrics in the process of green and digital environment transformation. To assess the exposure levels in shopping malls, we conducted a human centric extensive measurement campaign using three-axial frequency selective measurement equipment. Our study involved various indoor locations within the mall, capturing electrical field levels at different times and days of the week. A total of 529,340 samples were collected during working days, and 430,020 samples were collected during weekends. We measured E-field strength, power density, and calculated total exposures for frequency bands ranging from 88 MHz to 5850 MHz. The presented comparative analysis revealed that mobile communications technologies operating at 900 MHz and 1800 MHz were the main contributors to personal exposure levels in different mall environments.